Antibiotic Resistance and Sewage-Associated Marker Genes in Untreated Sewage and a River Characterized During Baseflow and Stormflow - Ahmed, Warish; Gyawali, Pradip; Hamilton, Kerry A.; Joshi, Sayalee; Aster, David; Donner, Erica; Simpson, Stuart L.; Symonds, Erin M. (Frontiers in Microbiology, 2021)
In this study, sewage treatment plant (STP) influent samples were collected and analysed using qPCR to investigate the abundance and correlations between sewage-associated markers (i.e., Bacteroides HF183, Lachnospiraceae Lachno3, crAssphage) and ARGs indicating resistance to nine antibiotics (belonging to aminoglycosides, beta-lactams, class 1 integrase, sulfonamides, macrolides, and tetracycline). All ARGs, except blaVIM, and sewage-associated marker genes were always detected in untreated sewage, and ermF and sul1 were detected in the greatest abundances. Class 1 integrase integron intl1 element was also highly abundant in untreated sewage samples. Significant correlations were identified between sewage-associated marker genes, ARGs and intl1 element in untreated sewage ( = 0.488, p = 0.0125). Of the three sewage-associated marker genes, the BIO-ENV procedure identified that HF183 alone best maximized correlations to ARGs and intl1 element ( = 0.590). Additionally, grab samples were collected from peri-urban and urban sites along the Brisbane River system during base and stormflow conditions, and analysed for E. coli, ARGs, intl1 element, and sewage-associated marker genes using qPCR. Significant correlations were identified between E. coli, ARGs, and intl1 element ( = 0.0893, p = 0.0032), as well as with sewage-associated marker genes in water samples from the Brisbane River system ( = 0.3229, p = 0.0001). Of the sewage-associated marker genes and E. coli, the BIO-ENV procedure identified that crAssphage alone maximized correlations with ARGs and intl1 element in river samples ( = 0.4148). Significant differences in E. coli, ARGs, intl1 element, and sewage-associated marker genes, and by flow condition (i.e., base vs. storm), and site types (peri-urban vs. urban) combined were identified (R = 0.3668, p = 0.0001), where percent dissimilarities between the multi-factorial groups ranged between 20.8% and 11.2%. Results from this study suggest increased levels of certain ARGs and sewage-associated marker genes in stormflow river water samples compared to base flow conditions. E. coli, HF183 and crAssphage may serve as potential indicators of sewage-derived ARGs under stormflow conditions, and this merits further investigation. Data presented in this study will be valuable to water quality managers to understand the links between sewage pollution and ARGs in urban environments.